2019
DOI: 10.3390/ijerph16162833
|View full text |Cite
|
Sign up to set email alerts
|

Association of lncRNA CCAT2 and CASC8 Gene Polymorphisms with Hepatocellular Carcinoma

Abstract: The worldwide incidence of hepatocellular carcinoma (HCC), the major histological type of primary liver cancer, is heterogeneous due to the variable prevalence of etiological factors, indicating a correlation of HCC risk with genetic variations among individuals. Among long non-coding RNAs (lncRNAs) located in the chromosome 8q24 loci and involved in the carcinogenesis are colon cancer associated transcript 2 (CCAT2) and cancer susceptibility candidate 8 (CASC8). In this study, the association of CCAT2 and CAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…Moreover, the possible role of lncRNA gene polymorphism in the risk of HCC was also explored, where data from a recent study demonstrated an inverse association of CASC8 gene polymorphisms, rs3843549, and rs13281615 with HCC progression and prognosis [82]. Collectively, lncRNAs gene polymorphism were associated with HCC with moderate epidemiological evidence and deserve further study and additional biological and clinical assessment.…”
Section: Potential Diagnostic and Therapeutic Applicationsmentioning
confidence: 99%
“…Moreover, the possible role of lncRNA gene polymorphism in the risk of HCC was also explored, where data from a recent study demonstrated an inverse association of CASC8 gene polymorphisms, rs3843549, and rs13281615 with HCC progression and prognosis [82]. Collectively, lncRNAs gene polymorphism were associated with HCC with moderate epidemiological evidence and deserve further study and additional biological and clinical assessment.…”
Section: Potential Diagnostic and Therapeutic Applicationsmentioning
confidence: 99%
“…The role of lncRNAs in various biological processes, such as cell differentiation, proliferation and apoptosis in various diseases, including cancer, has received increasing attention (10)(11)(12). The colon cancer associated transcript 2 (CCAT2) gene has been reported to be upregulated in various types of human cancer, including gastric cancer, non-small cell lung cancer, esophageal cancer (13)(14)(15)(16)(17), hepatocellular carcinoma (18,19) and other tumors (20)(21)(22), and it is associated with the occurrence and metastasis of cancer, as well as poor prognosis. Previous studies have demonstrated that lncRNA CCAT2 is localized in the 8q24 genomic region, which has been identified as the first reproducible genetic risk site (23,24).…”
Section: Introductionmentioning
confidence: 99%
“… 15 It has been observed that compared with the population with the rs10505477 TT genotype, those with TC or CC genotype were at significantly decreased risk of many types of cancer. 15 Correlations between CASC8 polymorphisms and risk of cancer have been reported in colorectal cancer, 16 hepatocellular carcinoma, 17 lung cancer, 13 and acute lymphoblastic leukemia. 18 However, the expression pattern and function of CASC8 in cancer biology remains unclear.…”
Section: Discussionmentioning
confidence: 99%